Single-Center Experience With Endovascular Treatment for Splenic Artery Aneurysms in Long-Term Follow-Up: A Retrospective Study - Cao, Yanyan; Song, Songlin; Ouyang, Tao; Zheng, Chuansheng (Frontiers in Cardiovascular Medicine, 2022)
Objectives To reveal a single-center experience with endovascular treatment for splenic artery aneurysm (SAA) and analyze the safety and efficacy of the operation in the long-term follow-up. Materials and Methods A total of 49 patients with SAAs (21 men, 28 women; mean age, 52.4 ± 11.5 years) were enrolled in this study from July 2010 to December 2020. Baseline and characteristics of SAAs were collected. Parent artery coil embolization or combined with sac coil embolization of SAAs, graft-stent implantation, or bare-stent-assisted coil embolization were performed for the treatment of SAAs. Adverse events and follow-up data were recorded. Results The average diameter of SAAs was 3.3 ± 2.5 cm (range, 1.0–13.6 cm). An individual-tailed modality was conducted for three patients. A 100% technical success rate was achieved. No re-intervention procedure was performed in all patients. No major treatment-related adverse events were observed, and no expansion or rupture of SAAs occurred in the average follow-up period of 57.9 ± 27.3 months (19–125 months). Conclusion Endovascular treatment of SAA, including the individual-tailed therapy for three cases, is safe, effective, and minimally invasive with high technical success rates and satisfactory outcomes during the long-term follow-up period.